Acute traumatic coagulopathy in a critically injured pediatric population: Definition, trend over time, and outcomes. Issue 1 (July 2016) - Leeper, Christine M.; Kutcher, Matthew; Nasr, Isam; McKenna, Christine; Billiar, Timothy; Neal, Matthew; Sperry, Jason; Gaines, Barbara A.
Abstract : BACKGROUND: While our understanding of acute traumatic coagulopathy (ATC) in adults is advancing, the pediatric literature on ATC is limited. Children have a unique injury profile and physiologic response to trauma; however, the impact of this phenomenon on ATC has not been fully elucidated. METHODS: We performed a retrospective review of our trauma registry from 2005 to 2014. Level 1 trauma patients age 0 year to 17 years requiring admission to the intensive care unit were included. Variables included admission vital signs and laboratory studies, product transfusion, injuries, and mortality. Youden index was used to determine optimum cutoff point for admission international normalized ratio (INR) as a predictor of mortality. Logistic regression modeling was used to determine independent predictors of mortality adjusting for hypotension, hypothermia, acidosis, injury severity, hemorrhage, and head injury. χ 2 tests were performed evaluating for association between mortality and 24-hour INR as well as between transfusion and INR correction. RESULTS: A total of 776 patients were analyzed: 29.2% (n = 227) had an admission INR of 1.3 or greater, and 13.3% (n = 103) had an admission INR of 1.5 or greater. Youden index demonstrated optimum cutoff at INR of 1.3 or greater to distinguish survivors and nonsurvivors. Overall mortality rate was 11.1% (n = 86). Elevated INR was independently associated with mortality (odds ratio, 3.77; p < 0.001) after controlling for other predictors in regression modeling. Death was also associated with elevated INR at 24 hours and worsening INR trend over time. Patients who received plasma were equally likely to normalize their INR compared with those who were not transfused ( p = nonsignificant). Findings were consistent across age groups. CONCLUSION: INR likely serves as a marker of systemic dysregulation rather than a treatment target in ATC. Elevated admission INR, elevated INR at 24 hours, and overall trend in INR strongly predict mortality in a diverse pediatric trauma population; however, product transfusion did not influence the INR trend or clinical outcome. Further research is warranted to evaluate potential upstream mediators of ATC and targets for intervention in pediatric trauma patients. LEVEL OF EVIDENCE: Prognostic and epidemiologic study, level III.